RDAP13 summit: Introduction. Issue 6 (12th August 2013) - Parham, Susan Wells; Rolando, Elizabeth; Doty, Jennifer
Abstract Editor's Summary This special section of the Bulletin explores issues in research data access and preservation (RDAP) and samples the program highlights and attendees' reflections of the ASIS&T RDAP13 Summit, the 4th annual meeting, held in Baltimore, Maryland, on April 4–5, 2013. Contributed papers address the value of partnering with publishers and repositories as a way to address the complexity of data curation and explore the issue of data use and reuse from a data curator's perspective. One article discusses the use, benefits and challenges of altmetrics to track citations of research data. Others tackle the need to develop a standard data infrastructure and describe efforts to promote research data management across institutions of higher education in the United Kingdom. Last, a sampling of the posters presented at RDAP13 reflects the scope of the topic, current progress and advances to come.